Faktor risiko kejadian stunting pada anak umur 6-36 bulan di Wilayah Pedalaman Kecamatan Silat Hulu, Kapuas Hulu, Kalimantan Barat - Siti Wahdah; M Juffrie; Emy Huriyati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Stunting in children under five is an indicator of nutritional status that can reflect problem of overall social economic condition in the past. Stunting that occurs in childhood is a risk factor of increasing in mortality rate, low cognitive capability and motoric development, and improper physical function. The incidence of stunting is associated with many factors such as family environment (education, occupation, income, rearing pattern, eating pattern, and number of family members), nutritional factors (exclusivebreastfeeding and duration of breastfeeding), genetic factor, infection disease, and the incidence of low birth weight. The scope of stunting in 2010 were 35,6% and 39,7% in Indonesia and Province of Kalimantan Barat.Objectives: To identify the risk factors associated with the incidence of stunting in children of 6-36 months in Silat Hulu District of Kapuas Hulu, Province of Kalimantan Barat.Methods: This was an analytic observational study with cross sectional design. Population of the study were all of underfi ves children at remote area of Subdistrict of Silat Hulu, District of Kapuas Hulu, Province of Kalimantan Barat. Data analysis used chi-square test and logistic regression analysis to identify themost dominantly determinant stunting variable.Results: The incidence of stunting was significantly associated with occupation of mother, height of father, height of mother, income, number of family members, rearing pattern, and exclusive breastfeeding supplementation (p<0.05). The incidence of stunting was not associated with occupation of father, eating pattern, duration of breastfeeding, infection disease, and education of mother (p>0.05).Conclusions: Factors associated with the incidence of stunting were the work of mothers, rearing pattern, family income, number of household members, father’s height, maternal height, and exclusive breastfeeding. The most dominant determinant of risk factors on the incidence of stunting were exclusivebreastfeeding, number of household members, maternal height, income, and father’s height.KEYWORDS: exclusive breastfeeding, height of father, height of mother, income, stuntingABSTRAKLatar belakang: Stunting pada anak balita merupakan indikator status gizi yang dapat memberikan gambaran gangguan keadaan sosial ekonomi secara keseluruhan di masa lampau. Stunting yang terjadi pada masa anak merupakan faktor risiko meningkatnya angka kematian, kemampuan kognitif dan perkembangan motorik yang rendah, dan fungsi tubuh yang tidak seimbang. Kejadian stunting berhubungan dengan berbagai macam faktor antara lain lingkungan keluarga (pendidikan, pekerjaan, pendapatan, pola asuh, pola makan dan jumlah anggota rumah tangga), faktor gizi (ASI eksklusif danlama pemberian ASI), faktor genetik, penyakit infeksi, dan kejadian BBLR. Menurut hasil riset kesehatan dasar, prevalensi anak balita yang menderita stunting di Indonesia pada tahun 2010 masih tinggi sebesar 35,6%, dan 39,7% di Provinsi Kalimantan Barat.Tujuan: Mengetahui faktor risiko yang berhubungan dengan kejadian stunting pada anak umur 6-36 bulan di pedalaman Kecamatan Silat Hulu, Kabupaten Kapuas Hulu, Provinsi Kalimantan Barat.Metode: Penelitian ini merupakan penelitian observasional analitik dengan rancangan cross sectional. Populasinya adalah seluruh balita yang ada di wilayah pedalaman Kecamatan Silat Hulu Kabupaten Kapuas Hulu Provinsi Kalimantan Barat. Analisis data menggunakan uji chi-square dan untuk mengetahui variabel paling determinan terhadap stunting dilakukan analisis regresi logistik.Hasil: Kejadian stunting berhubungan signifi kan dengan pekerjaan ibu, tinggi badan ayah, tinggi badan ibu, pendapatan, jumlah anggota rumah tangga, pola asuh, dan pemberian ASI eksklusif (p<0,05). Kejadian stunting tidak berhubungan dengan, pekerjaan ayah, pola makan, lama pemberian ASI, penyakit infeksi, dan pendidikan ibu (p>0,05).Kesimpulan: Faktor yang berhubungan dengan kejadian stunting adalah pekerjaan ibu, pola asuh, pendapatan keluarga, jumlah anggota rumah tangga, tinggi badan ayah, tinggi badan ibu, dan pemberian ASI eksklusif. Faktor risiko determinan terhadap kejadian stunting adalah pendapatan, jumlah anggotarumah tangga, tinggi badan ayah, tinggi badan ibu, dan pemberian ASI eksklusif.KATA KUNCI: stunting, pendapatan, jumlah anggota rumah tangga, tinggi badan, ayah, tinggi badan ibu, pemberian ASI eksklusif